Design and Creation of Application Estimation of Wood Packing Service Cost for Web-Based Goods Delivery With Prototype Model (Case Study: PT. Cahaya Lintang Lestari) - Albian, Dava; Widya Sudarto, Annisa; Rahman Aziz, Farid; Haryono, Wasis (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The development of information technology has driven the need for information systems that can improve efficiency and accuracy in business operations. PT Cahaya Lintang Lestari, a company engaged in logistics packaging services, still uses traditional methods such as manual recording and Excel in calculating estimated wooden packing costs. This method often causes errors and is less efficient. To overcome this, a web-based application was developed with a prototyping method, which aims to calculate estimated packing costs automatically. The system development process is carried out in stages in six stages, starting from gathering needs to the implementation stage. This application makes it easy for customers to obtain price estimates independently without having to contact the service provider, and facilitates integrated data management. Based on the implementation results, this system has been proven to improve calculation accuracy, speed up the service process, and provide price transparency to customers. Overall, the use of this system can improve the quality of service and the company’s operational efficiency.